Roots of Cultural Diversity - Oded Galor; Marc Klemp; Daniel Crisóstomo Wainstock (Institute of Labor Economics (IZA), 2024)
This study reveals the pivotal impact of the prehistoric out-of-Africa migration on global variation in the degree of cultural diversity within ethnic and national populations. Drawing on novel diversity measures—encompassing folkloric and musical traditions among indigenous ethnic groups, as well as norms, values, and attitudes in modern societies—an intriguing pattern emerges: societies whose ancestors migrated farther from humanity's cradle in Africa exhibit lower cultural diversity. These striking findings underscore: (i) the profound role of cultural dynamics in shaping the enduring effects of the out-of-Africa migration on social cohesion, innovativeness, and living standards; (ii) the origins of persistent global variations in cultural expressions within an increasingly interconnected world; and (iii) the roots of variations in societal adaptability to evolving economic and technological landscapes.
Keywords: O10; Z10; 330; diversity; culture; out-of-africa; folkloric diversity; musical diversity; social norms